Challenges Facing Learning Neighborhood Centers in the Riyadh Region - Alarifi, Norah Saad; Al-Battal, Dalal Abdullah; Al-Khudair, Amani Abdullah; Al-Subaie, Taghreed Farraj (Journal of Educational and Psychological Sciences, 2022)
This study aims to know the challenges facing the learned neighborhood centers in digital literacy in the Riyadh region, by identifying the administrative, social and economic challenges facing the learned neighborhood centers in digital literacy for adults, The study used the descriptive survey method, and the study sample consisted of all the heads of adult education units in the education offices in Riyadh, who numbered (9), and the supervisors of the learning neighborhood centers numbered (3), and the directors of the learning neighborhood centers in Riyadh, which numbered (7). Following the comprehensive enumeration method, by applying the study tool to the entire study population; After the field application, (33) valid questionnaires were obtained for statistical analysis. Most Significant Results of the study: The need to implement a variety of digital training programs in the educated neighborhood centers that help adults. and The shortcomings in the availability of digital literacy training packages in adult education departments.The small number of learner neighborhood centers affiliated with adult education centers in the Riyadh region. Inadequate follow-up of education offices and the Department of Adult Education in the implementation of digital literacy programs implemented in the learning neighborhood centers, the difficulty of the procedures to enroll in digital literacy programs in the learning neighborhood centers. and The need for the educated neighborhood centers to contribute to educating and training adults to keep pace with the labor market in digital programs. Based on the results, the researchers recommended planning to implement various digital training programs in the centers of the learning neighborhood, providing training packages for eradicating digital illiteracy in the adult education departments, increasing the number of the centers of the learning neighborhood, and establishing a community partnership with other parties in implementing digital education programs in the centers of the learned neighborhood, in addition to proposals for future studies; About the challenges facing the centers of the educated neighborhood and ways to reduce them.